RETRACTED: Results of mathematical modelling of the cooling system for solar panels of a hybrid power plant based on solar and hydraulic energy - Bozarov Oybek; Aliev Rayimjon; Kuchkarov Akmaljon; Goipov Elmurod; Kuchkarova Mahmudahon (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001